Students’ perceptions of lecturer feedback in writing thesis proposal - Taufik Suadiyatno; Arrafii, Moh. Arsyad (Journal of English Language Proficiency, 2025)
This study investigates the role of lecturer feedback in developing writing thesis proposal among foreign-language learners in the English Education Department at Mandalika University of Education. It explores students' perceptions of the types of feedback that best enhance their abilities writing thesis proposal. This study involved fourteen students of that have been conducting their thesis proposal. Two instruments were used to collect the data; questionnaires and interviews. The research reveals that students value feedback for error correction, improving grammar, and boosting writing quality. Feedback also plays a key role in motivating and building students' confidence. The findings show that students prefer direct feedback that targets detailed mistakes. Overall, the study highlights the importance of effective feedback in writing development and provides insights for lecturer to tailor their students.